Landiolol for managing post-operative atrial fibrillation - Balik, Martin (Eur Heart J Suppl, 2018)
Beta-blockers are a potential option to manage peri-operative atrial fibrillation. Landiolol is a new ultra-short beta-blocker with a half-life of only 4 minutes and very high beta-1 selectivity which has been used for treatment and prevention of atrial fibrillation in pulmonary surgery and gastro-intestinal surgery. Due to its limited negative inotropic effect and high beta-1 selectivity landiolol allows for control of heart rate with minimal impact on blood pressure. Landiolol is well tolerated by the respiratory system. Additional benefits are related to the regulation of the inflammatory response and blunting of the adrenergic pathway. There is a limited number of trials with total of 61 patients undergoing lung resection or oesophagectomy who developed post-operative atrial fibrillation and were treated with landiolol. The experience with landiolol for prevention is more documented than landiolol application for treatment of post-operative atrial fibrillation. There are 9 comparative studies with a total of 450 patients administered landiolol for prevention of post-operative atrial fibrillation. The use of low dosage (5-10mcg/kg/min) is usually sufficient to rapidly control heart rate which is associated with earlier and higher rate of conversion to sinus rhythm as compared to the controls. The excellent tolerance of landiolol at lower dosage (3-5mcg/kg/min) allows to initiate prophylactic use during surgery and postoperatively. Landiolol prophylaxis is associated with reduced incidence of post-operative atrial fibrillation without triggering adverse events related to a beta-blockade.